Choose us, we are different! Free schools’ self-descriptions and -positioning in the Swedish educational system - Jakob Billmayer (Utbildning & Demokrati)
Since the beginning of the 1990s, Swedish parents have had the possibility of choosing schools for their children based on publicly funded school vouchers. At the same time, free schools started to develop, competing for the pupils. Even though the free schools are a part of the educational system, obligated to follow the same rules as the public schools, they describe themselves as different, something outside the system yet inside the system. The aim of the paper is to analyse and discuss the different strategies of integration into and differentiation within the educational system. Economic theory on competition and differentiation strategies is used to analyse the content of the three largest free school companies’ websites. The free schools mainly integrate into the legal aspects of the educational system and differentiate themselves from other schools by making claims about qualitative superiority. Different free schools position themselves differently relative to the educational system.